DIY Aging: Retirement Migration as a New Age-Script - Liesl L. Gambold (Anthropology & Aging, 2018)
The post-retirement aging process involves making many decisions. Strained social welfare programs for the elderly have met with a generation well-versed in ‘do-it-yourself’ projects resulting in a novel script for DIY retirement, aging and dying. For decades baby boomers in North America and Europe have valorized personal freedom and independence and are now carrying these values into retirement. Some are seeking tenable, independent retirement options abroad in response to inadequate retirement savings, a fear of rising medical costs and lack of faith in local and state systems. Based on ethnographic research among diverse retirees in North America and Europe this paper argues that age-inscriptions and retirement are actively being rewritten by those compelled to DIY.